Making watercress (Nasturtium officinale) cropping sustainable: genomic insights into enhanced phosphorus use efficiency in an aquatic crop - Hibbert, Lauren E.; Qian, Yufei; Smith, Hazel K.; Milner, Suzanne; Katz, Ella; Kliebenstein, Daniel J.; Taylor, Gail (Frontiers in Plant Science, 2023)
Watercress (Nasturtium officinale) is a nutrient-dense salad crop with high antioxidant capacity and glucosinolate concentration and with potential to contribute to nutrient security as a locally grown outdoor aquatic crop in northern temperate climates. However, phosphate-based fertilizers used to support plant growth contribute to the eutrophication of aquatic habitats, often pristine chalk streams, downstream of farms, increasing pressure to minimize fertilizer use and develop a more phosphorus-use efficient (PUE) crop. Here, we grew genetically distinct watercress lines selected from a bi-parental mapping population on a commercial watercress farm either without additional phosphorus (P-) or under a commercial phosphate-based fertilizer regime (P+), to decipher effects on morphology, nutritional profile and the transcriptome. Watercress plants sustained shoot yield in P- conditions, through enhanced root biomass, but with shorter stems and smaller leaves. Glucosinolate concentration was not affected by P- conditions, but both antioxidant capacity and the concentration of sugars and starch in shoot tissue was enhanced. We identified two watercress breeding lines, with contrasting strategies for enhanced PUE: line 60, with highly plastic root systems and increased root growth in P- and line 102, maintaining high yield irrespective of P supply, but less plastic. RNA-seq analysis revealed a suite of genes involved in cell membrane remodeling, root development, suberization and phosphate transport as potential future breeding targets for enhanced PUE. We identified watercress gene targets for enhanced PUE for future biotechnological and breeding approaches enabling less fertilizer inputs and reduced environmental damage from watercress cultivation.